Intercultural transformation stages by Thai EFL tertiary learners in Facebook comments / Suhaila Etae - Etae, Suhaila (2019)
Students encounter with the influence of Thai culture in English communication. Through their studies of English, the students have been exposed to Western-learned culture affected by their Thai innate culture. This EFL learning condition shapes intercultural transformation occurred in intercultural communication in Thai context. Therefore, the aim of this paper is to explore intercultural transformation stages made by the Thai students in Facebook comment boxes posted to a Thai lecturer teaching English reading. Data was qualitatively collected from the students’ Facebook comments which was required as a participation during learning of Analytical and Critical Reading course posted to the lecturer. The obtained results indicated that the most significant stage of intercultural communication made by the student participants was stage 1 “poor psychological health”, followed by stage 2 “functional fitness”, stage 3 “fit psychological health” and stage 4 “intercultural identity”. For the cultural transformation, collectivism affected the students’ intercultural shifts in posting the FB comments to communicate in English with the lecturer.